Implementasi Program Tahfizh Qur’an Di PAUD Inklusif Dengan Model HOTS - Enung Nugraha (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2020)
Introducting Al-Qur'an has done by cooperation of parents and teachers which tahfizh Al-Qur'an interacting on daily consolidated. Tahfizh Qur'an is a religious program to improve children's concentration and learning outcomes. HOTS model approach an important role. The study to determine the implementation tahfizh Qur'an program in early childhood by higher order thinking skills (HOTS) model. The method used literature study approach. The tahfizh program in early childhood is part of religious and character education so that children memorize, deepen meaning and empathy, get used to at school and home. Teachers can apply higher order thinking skills learning models, not only evaluating the memorization of the Qur'an but until students act to do something and even become used to it. Implementatign of tahfizh Qur'an program in early childhood using HOTS model is important for teachers at school and guided by parents at home so habituation besides increasing concentration also fosters empathy. Keywords: inclusive PAUD; tahfizh Qur’an; HOTS References Afandi, Akhyar, S. (2017). Stimulan Keterampilan Tingkat Tinggi. UNS Press. Ahsin W. (2004). Bimbingan praktis menghafal Al-Qur’an (Nomor 101). Bumi Aksara. Ariyanti Novelia Candra, Ari Sofia, G. F. A. (2017). Gaya Pengasuhan Orang Tua pada Anak usia Dini Ariyanti. Jurnal Pendidikan Anak., 3(2), 1689–1699. https://doi.org/10.1017/CBO9781107415324.004Azizah, A. N., Adriany, V., & Romadona, N. F. (2019). Penyelenggaraan Pendidikan Inklusif di Lembaga PAUD. Edukids: Jurnal Pertumbuhan, Perkembangan, dan Pendidikan Anak Usia Dini, 16(2), 109–120. Dinni, H. N. (2018). HOTS ( High Order Thinking Skills ) dan Kaitannya dengan Kemampuan Literasi Matematika. Prisma, 1, 170–176. Ferdinan, F. (2018). Pelaksanaan Progam Tahfidz Al Qur’an (Studi Pesantren Darul Arqam Muhammadiyah Gombara Sulawesi Selatan). TARBAWI : Jurnal Pendidikan Agama Islam, 3(01), 37–50. https://doi.org/10.26618/jtw.v3i01.1379Gunawan, A. (2018). Teologi Surat al-Maun dan Praksis Sosial Dalam Kehidupan Warga Muhammadiyah. SALAM: Jurnal Sosial dan Budaya Syar-i, 5(2), 161–178. https://doi.org/10.15408/sjsbs.v5i2.9414Heldanita. (2016). Konsep Pendidikan Inklusif Pada Lembaga Pendidikan Anak Usia Dini. Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 1(3), 15–24. Hidayah, N. (2016). Strategi Pembelajaran Tahfidz Al-Qur’an di Lembaga Pendidikan. Ta’allum: Jurnal Pendidikan Islam, 4(1), 63–81. https://doi.org/10.21274/ taalum.2016.4.1.63-81Hidayat, F. (2017). Kajian Psikologi Pembelajaran Hafal Quran bagi Anak Usia Dini. Proceedings of The 2nd Annual Conference on Islamic Early Childhood Education, 2, 83–94. Hidayat, F. (2016). Pengasuhan Anak Usia Dini Dalam Perspektif Psikologi. Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa, 1–4. Hidayat, F., & Imroatun, I. (2018). Keluarga Berencana Dan Pengasuhan Anak Usia Dini Di Indonesia Perspektif Psikologi. International Conference Proceeding Konsepsi dan Implementasi Pendidikan Islam Anak Usia Dini Book two, 164–171. Huliyah, M. (2016). Hakikat Pendidikan Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 60–71. Imam Nawawi. (2010). Taliq ala Muqaddima al-Majmu’ lil Nawawi - Al-Uthaymin. Daar El Fikri. Imroatun, I. (2017a). Anak Dengan Kebutuhan Fisik Khusus. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(2), 175–185. Imroatun, I. (2017b). ANAK DENGAN KEBUTUHAN FISIK KHUSUS. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(2), 175–185. Imroatun, I., Nirmala, I., Juhri, J., & Muqdamien, B. (2020). Kajian Literatur Pengasuhan Anak Usia Dini Dalam Islam. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(1), 57–66. https://doi.org/10.32678/AS-SIBYAN.V5I1.2703Indira, E. W. . (2019). Kurikulum PAUD Inklusi Dalam Menghadapi Era Industri 4.0. Prosiding Seminar Nasional Pascasarjana UNNES, 575–578. Islamiah, F., Fridani, L., & Supena, A. (2019). Konsep Pendidikan Hafidz Qur’an pada Anak Usia Dini. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 3(1), 30–38. Jazariyah. (2016). Urgensi Program Parenting dalam Implementasi PAUD. Proceedings of The 1st Annual Internasional Conference on Islamic Early Childhood Education, 41–48. Lubis, A., & Ismet, S. (2019). Metode Menghafal Alquran Pada Anak Usia Dini di Tahfidz Center Darul Hufadz Kota Padang. Aulad : Journal on Early Childhood, 2(1), 8–14. Maulipaksi, D. (2017). Sekolah Inklusi dan Pembangunan SLB Dukung Pendidikan Inklusi. Kemendikbud RI. https://www.kemdikbud.go.id/main/blog/2017/02/ sekolah-inklusi-dan-pembangunan-slb-dukung-pendidikan-inklusiMetafisika, K. (2019). Penilaian Keterampilan Bertanya Calon Guru PAUD sebagai Strategi Pengembangan Kognitif Anak Usia Din. Child Education Journal, 1(2), 88–95. Musaropah, U. (2016). Pemberdayaan Masyarakat Dalam Penyelenggaraan Pendidikan Anak Usia Dini Berbasis Pesantren. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 177–185. Nadirah, Y. F. (2016). Mengoptimalkan Otak Anak Sejak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 186–195. Najib, M. (2018). Model Manajemen PAUD Berdaya Saing Studi Pada Lembaga PAUD Islam Terpadu Al-Ikhlas Bumiayu Kabupaten Brebes. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(2), 125–136. Nata, A. (2015). Akhlak Tasawuf dan Karakter Mulia. Rajawali Press. Nuryati, N. (2017). Pengembangan Kecerdasan Spiritual Pada Anak Usia Dini Melalui Murottal Bacaan Al-Quran. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(1), 17–26. Pamungkas Stiyamulyani, P. S., & Sri Jumini, S. J. (2018). Pengaruh Menghafal Al-Qur’an Terhadap Highorder Thingking Skils (Hots) Ditinjau Dari Motivasi Berprestasi Mahasiswa. SPEKTRA : Jurnal Kajian Pendidikan Sains, 4(1), 25. https://doi.org/10.32699/spektra.v4i1.43Usmaedi, U. (2017). Menggagas Pembelajaran HOTS Pada Anak Usia Sekolah Dasar. Jurnal Pendidikan Sekolah Dasar, 3(1), 82. https://doi.org/10.30870/jpsd.v3i1.1040Wiani, N. A. (2018). Konsep Manajemen PAUD Berdaya Saing. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(1), 25–44. Widodo, T., & Kadarwati, S. (2013). HIGHER ORDER THINKING BERBASIS PEMECAHAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR BERORIENTASI PEMBENTUKAN KARAKTER SISWA Tri. Cakrawala Pendidikan, 32(1), 161–171.